2018
DOI: 10.3892/ol.2018.9327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of let‑7c on the proliferation of ovarian carcinoma cells by targeted regulation of CDC25a gene expression

Abstract: Abstract. MicroRNAs serve a role in the development of ovarian cancer (OC). The present study investigated whether let-7c is able to regulate the proliferation of OC cells by targeting cell division cycle 25A (CDC25a). The reverse transcription-quantitative polymerase chain reaction was performed to detect the expression of let-7c in OC specimens. Let-7c agomir was transfected into OC cells, and the proliferation and apoptosis of OC cells were detected. A dual-luciferase assay and western blotting were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…It has been reported in a variety of solid tumors that let-7c-5p acts as a tumor suppressor, inhibiting cell proliferation, migration and invasion. [18][19][20][21][22][23] Although cluster analysis has found that let-7c is downregulated in ESCC tissues, the specific role and underlying mechanisms of let-7c in ESCC have not been further elucidated. To explore the mechanism of let-7c-5p in ESCC, first, we confirmed that let-7c-5p was clearly downregulated in ESCC tissues and five ESCC cell lines (TE-1, TE10, TE11, KYSE140 and KYSE150) compared to normal tissues and cells, which was consistent with the previously reported cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in a variety of solid tumors that let-7c-5p acts as a tumor suppressor, inhibiting cell proliferation, migration and invasion. [18][19][20][21][22][23] Although cluster analysis has found that let-7c is downregulated in ESCC tissues, the specific role and underlying mechanisms of let-7c in ESCC have not been further elucidated. To explore the mechanism of let-7c-5p in ESCC, first, we confirmed that let-7c-5p was clearly downregulated in ESCC tissues and five ESCC cell lines (TE-1, TE10, TE11, KYSE140 and KYSE150) compared to normal tissues and cells, which was consistent with the previously reported cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] The miRNA let-7, one of the earliest identified human miRNAs, participates in various biological processes such as cell proliferation, differentiation, apoptosis, hormone secretion, metabolism, immune regulation and tumorigenesis. Recent studies have found that let-7c-5p is significantly downregulated in a variety of human malignant tumors, including head and neck squamous cell carcinoma, 18 nonsmall cell lung cancer, 19 hepatocellular carcinoma, 20 colorectal cancer, 21 ovarian carcinoma 22 and glioma. 23 Importantly, based on the results of unsupervised hierarchical clustering in previous literature, it was found that let-7c was downregulated in ESCC tissues.…”
Section: Introductionmentioning
confidence: 99%